Effects of three different formulae of Gamisoyosan on lipid accumulation induced by oleic acid in HepG2 cells - Go, Hiroe (Integr Med Res, 2017)
BACKGROUND: Gamisoyosan (GSS) is an herbal formula which has been used to treat women’s diseases for several hundred years in Korea. GSS is one of the three most common prescriptions among women and is used to treat menopausal symptoms. Fatty liver disease is also common in postmenopausal women and can precede more severe diseases, such as steatohepatitis. The present study compared the effects of GSS on fatty liver using three different formulae, Dongui-Bogam (KIOM A), Korean Pharmacopeia (KIOM B) and Korean National Health Insurance (KIOM C). METHODS: In oleic acid-induced HepG2 fatty liver cells, cellular lipid accumulation, triglycerides and total cholesterol were measured after treatment with three GSS formulae and simvastatin as a positive control. To investigate the phytoestrogen activity of GSS, MCF-7 cells were treated with GSS, and hormone levels were quantified. Also, qualitative analysis was performed with UPLC. RESULTS: All types of GSS decreased cellular lipid accumulation. KIOM A was slightly less effective than the other two GSS formulae. KIOM B and KIOM C decreased cellular triglycerides more effective than simvastatin, but KIOM A did not affect cellular triglycerides. Cellular total cholesterol was decreased by all GSS and simvastatin. GSS showed phytoestrogen activity in MCF-7 cells. From the UPLC analysis data, geniposide, paeoniflorin and glycyrrhizin were detected form three GSS formulae. CONCLUSION: These results suggest that all GSS formulae have a beneficial effect on fatty liver disease during menopause and that differences of formula have no effect on the efficacy of the prescription.